Posted - Anderson, John David, 1975- (Walden Pond Press, 2018)
After cell phones are banned at Branton Middle School, Frost, Deedee, Wolf, and Bench decide to start communicating with each other through sticky-notes, replacing text messages. It quickly catches on in the rest of the school, but for every nice note there is a mean, bullying one. Then, when new girl Rose sits down at Frost's lunch table, her presence threatens to unravel Frost's circle of friends, and the sticky-note war escalates.